ANALISIS KUAT TEKAN BETON PADA STRUKTUR GEDUNG MADRASAH ALIYAH JOMBANG - Sudarso, Sudarso; Maulana, Fahmi (Fakultas Teknik Universitas Palangka Raya, 2026)
This study is motivated by the importance of concrete quality control to ensure the safety and performance of building structures, particularly in the construction of Madrasah Aliyah Jombang. The objective of this research is to analyze the compressive strength of concrete and evaluate its conformity with the design strength of K-250. The method used is a quantitative approach through laboratory experiments by testing the compressive strength of cylindrical specimens at various ages. Samples were taken from several structural elements, including bore piles, pile caps, tie beams, columns, and working slabs. The results indicate that the compressive strength values are within and slightly exceed the planned strength, with a general trend of increasing strength as the concrete ages. Although minor fluctuations occur at certain ages, the overall pattern shows stability at later ages. These findings suggest that the material quality, mix composition, and construction practices have met the required standards. The results of this study can serve as a reference for quality control in similar construction projects to ensure structural safety and performance.